The Characterization of the Hydrophobic Surface of Nanocomposites Aloe vera/PS for Antimicrobial Pathogens - Lathifa Zonesya Putri; Ratnawulan Ratnawulan; Ramli Ramli; Hamdi Rifai; Faridah Lisa Supian; Irna Humairah (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2023)
The spread of pathogenic microorganisms on a large scale creates a health disaster for the world. Modifying the surface of the fabric so that it is antimicrobial pathogens with hydrophobic properties is one solution to inhibit the spread of microorganisms. Surface modification was carried out using Aloe vera powder as filler and polystyrene matrix with Aloe vera:PS composition variations of 1:5, 2:5, and 3:5 using the dip coating method and drying temperatures of 10◦C, 50◦C, and 90◦C. The characterization results that have been carried out with the best composition variations are 3:5 and 50◦C with a layered morphology using Scanning Electron Microscopy (SEM), resulting in a surface particle size of 21.243 nm, large contact angle/WCA using a Canon D350 camera with a size of 150.23◦, Fourier Transmission Infrared Analysis (FTIR) with the dominant functional group in the vibration band 2629 cm−1 indicates the presence of a long hydroxyl chain, the vibration band 1500 cm−1 with C-H stretching of the aromatic ring is caused by the characteristics of the polystyrene polymer and the wave number is 1700 cm−1 with stretching C=O which shows the characteristics of the carbonyl group in the Aloe vera sample is a flavonoid compound. The resistance of Aloe vera/PS solution to Klebsiella pneumonia resulted in a 20.18 mm diameter barrier showing strong resistance against bacteria and X-Ray Diffraction analysis showed that the AV powder was amorphous. Thus, the AV/PS 3:5 composition with a calcination temperature of 50◦C represents the greatest variation in the synthesis and characterization of hydrophobic thin films for pathogenic antimicrobial organisms.